Estudantes guineenses na Universidade Federal de Uberlândia sociabilidade de identificações em terras do além-mar - Peixoto, Maria Denize Santos (2014)
The main aim of this paper is to analyze social experiences, perceptions and interactions of individuals from Guinea-Bissau at Federal University of Uberlândia as part of the Programa Estudante-Convênio de Graduação/ PEC G (programme for undergraduate students at partner institutions) with the assumption that they re-signify their identities while in temporal dislocation, and hence experience new forms of sociation. By means of a case-study, this paper examines the form(s) of sociability established by them. Methodologically, the option made herein was one for simple observation, questionnaires and semi structured interviews. First, I proceed with a brief review of the literature on the geopolitical, historical and sociocultural context in Guinea-Bissau. From a theoretical viewpoint, the relation between individual and society in the we I balance as conceptualized by Norbert Elias has underpinned the perspective herein of identity and difference as relational, multicultural and non-essentialized. Conceptual intakes from Georg Simmel and Jean Baechler are the references which have led this paper to the understanding of social interactions, and to suggest an equivalence of exchanges and strong links in the shaping of social networks. In systematizing the data built throughout the research, strategies of identification and social interaction arising from the students conversations in Creole and other diacritical traits laden with symbolism indicate a sense of unification and belonging, and identify form(s) of sociability of individuals in temporal dislocation.